(untitled) (Nordic Journal of African Studies, 2005)
Most of the world’s languages lack electronic word form dictionaries. The linguists who gather such dictionaries could be helped with an efficient morphology workbench that adapts to different environments and uses. A widely usable workbench could be characterized, ideally, as generally applicable, extensible, and freely available (GEA). It seems that such a solution could be implemented in the framework of finite-state methods. The current work defines the GEA desiderata and starts a series of articles concerning these desiderata in finite-state morphology. Subsequent parts will review the state of the art and present an action plan toward creating a widely usable finite-state morphology workbench.